2021
DOI: 10.1146/annurev-matsci-080819-125403
|View full text |Cite
|
Sign up to set email alerts
|

Gallium Liquid Metal: The Devil's Elixir

Abstract: Gallium is a metal that literally melts in your hand. It has low toxicity, near-zero vapor pressure, and a viscosity similar to water. Despite possessing a surface tension larger than any other liquid (near room temperature), gallium can form nonspherical shapes due to the thin, solid native oxide skin that forms rapidly in oxygen. These properties enable new ways to pattern metals (e.g., injection and printing) to create stretchable and soft devices with an unmatched combination of mechanical and electrical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
151
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(151 citation statements)
references
References 149 publications
0
151
0
Order By: Relevance
“…From the positive point of view, it can help Ga control its shape and size and form a core-shell structure for further functionalization. Tang et al considered the Ga native oxide layer as a platform for enhanced reactivity and systematically demonstrated the function of electrochemically driven reversible transition between Ga and Ga oxide layer on a wide range of reactions such as energy harvesting, soft robotics, field-effect transitors, soft diodes and memristors [157]. Liu et al also demonstrated in detail the surface engineering strategy by synthesizing core-shell LM materials for improved performance in several attractive scenarios including but not limited to soft electronics, nano/biomedicine, catalysis and energy storage/conversion [158].…”
Section: Discussionmentioning
confidence: 99%
“…From the positive point of view, it can help Ga control its shape and size and form a core-shell structure for further functionalization. Tang et al considered the Ga native oxide layer as a platform for enhanced reactivity and systematically demonstrated the function of electrochemically driven reversible transition between Ga and Ga oxide layer on a wide range of reactions such as energy harvesting, soft robotics, field-effect transitors, soft diodes and memristors [157]. Liu et al also demonstrated in detail the surface engineering strategy by synthesizing core-shell LM materials for improved performance in several attractive scenarios including but not limited to soft electronics, nano/biomedicine, catalysis and energy storage/conversion [158].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the development of materials science, various unique effects of soft matter have been gradually discovered and utilized. In particular, room-temperature liquid metals possess many favorable properties [20][21][22][23][24][25][26] , including large surface tension, ideal flexibility, high conductivity, low toxicity and so on. Furthermore, their excellent electric conductivity molds them into intrinsically conductive fluids.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 [27] lists some of the typical properties of gallium-based liquid metal and comparative liquids. Due to the different component ratios, the physical properties of such liquid metals appear somewhat different [22,23,25,26] . It should be noted that systematic measurements and currently available data for these materials remain rather limited.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, RTLM rechargeable batteries have become straightforward alternative energy storage devices. Gallium (Ga), a post-transition metal with a melting point of 29.8 °C, is one of the most interesting elements in the periodic table [ 15 ]. Ga has a water-like bulk viscosity of 1.99 mPa·s (vs. 1 mPa·s for water) [ 1 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gallium (Ga), a post-transition metal with a melting point of 29.8 °C, is one of the most interesting elements in the periodic table [ 15 ]. Ga has a water-like bulk viscosity of 1.99 mPa·s (vs. 1 mPa·s for water) [ 1 , 15 ]. Yamaguchi et al reported the reversible size control of gallium liquid metal nanoparticles (LMNPs) through ultrasonication [ 7 ].…”
Section: Introductionmentioning
confidence: 99%